Assessment of Difficulties in Breastfeeding in Infants below 6 months of Age - Sultana, Shamima; Sufian, Abu; Rahman, Saida Binte; Hossain, Salma; Kabir, Farzana; Das, Joyshree (Eastern Medical College Journal, 2022)
Background: Breast milk is very much essential for proper growth, development and wellbeing of children. They should be breastfed within 1 hour of birth, exclusively breastfed for first six months of life. Breastfeeding difficulties are common. Maternal, infant and social factors are involved in establishment of proper breastfeeding. Objective: To find out the difficulties that a mother face during breastfeeding. Methodology: Cross-sectional observational study was carried out Shaheed Suhrawardy Medical Collage & Hospital (Sh.S.MCH). All children upto 6 months of age and their mother attending in OPD, Breast feeding corner and pediatrics indoor of Sh.S.MCH during study period. Results: Total 19 (38%) infants had difficulty in breast feeding related to maternal factors. Majority (63%) of mother complained of not enough milk, but urine output of infants was ≥6 times within 24 hours in 7 infants of these mothers. Three mothers had stopped breast feeding due to sickness. Total 25 (50%) infants had difficulty in breast feeding related to infant factors. Majority 17 (68%) of them were crying babies, but urine output was ≥6 times in 24 hours in 12 of these infants. Refusal of breast was found in 6 (24%) infants, sickness was cause for stopping breastfeeding found in 2 (8%) infants. Total 13 (26%) infants had difficulty in breast feeding related to social factors. Majority 8 (67%) were working mother and 5 (33%) mothers said that there was lack of familial support. Conclusion: Most of the mothers initiated breast feeding 1 hour after birth. Most of the mothers had given honey as prelacteal feeding to their infants. Most of them were on partial breast feeding. Sixty five percent infants were given formula milk. Difficulties in breast feeding were related to infant factors and maternal factors mostly. More than one factor was present in some infant. EMCJ. January 2022; 7(1): 11-14